Implementation of learning reading and writing activities for 5th class students - La Rabani; Mansyur M (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The school literacy movement is a social movement that combines various components. The government has launched that schools carry out reading and writing learning activities as a "School Literacy Movement" This study aims to determine the implementation of reading and writing learning activities for grade V students of SD Negeri 37 Kediri City. Study this use study qualitative descriptive. In the survey, qualitative data was collected character qualitative, which describes the research setting, the situation, and the informant/respondent. Both in terms of saying or writing words into complete sentences for fifth-grade students at SD Negeri 37 Kendari City, from the results of observations in the Even Semester of the 2021/2022 Academic Year, it is known that the score The average daily test is only 65. Therefore, it is concluded that the reading ability in students' literacy learning activities is still relatively low or can be said to be below the Minimum Completeness Criteria (KKM) set at SD Negeri 37 Kendari City, which is 70.